1969
DOI: 10.2134/agronj1969.00021962006100020021x
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Pastures Improved with Sod‐seeding and Fertilization1

Abstract: ‘Emerald’ crownvetch (Cornilla varia L.) and ‘Viking’ birdsfoot trefoil (Lotus corniculatus L.) were sod‐seeded into permanent bluegrass pastures. Three types of sod openers were evaluated along with the use of paraquat sprayed in a 15‐cm band over the seeded row to reduce competition from the existing sod. Forage production from these sod‐seeded treatments was compared with complete renovation and seeding to a mixture of orchardgrass (Dactylis glomerata L.), ladino clover (Trifolium repens L.) and red clover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1974
1974
2001
2001

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Blowes et al (1985) demonstrated that, under field conditions, glyphosate did not reduce the growth of planted legumes when they were planted after glyphosate was applied at 0.54 and 1.08 kg a.i. ha −1 There have also been reports of successful establishment of legumes into existing pastures without using herbicides to suppress competing vegetation (Decker et al, 1969; Taylor and Allinson, 1983).…”
mentioning
confidence: 99%
“…Blowes et al (1985) demonstrated that, under field conditions, glyphosate did not reduce the growth of planted legumes when they were planted after glyphosate was applied at 0.54 and 1.08 kg a.i. ha −1 There have also been reports of successful establishment of legumes into existing pastures without using herbicides to suppress competing vegetation (Decker et al, 1969; Taylor and Allinson, 1983).…”
mentioning
confidence: 99%
“…In Australia, sur• face sowing of pasture species with the use of herbicides for sod control has produced adequate stands (3). In the United States, several researchers have reported successful interseeding when using sod-seeding drills and paraquat (1,1'-dimethyl-4,4'-bipyridinium ion) for sod suppression (2,6,12).…”
mentioning
confidence: 99%
“…L EGUMES are important in permanent pastures for high forage yield (2,5,6). Productivity of pastures with shallow soils has been found to be closely associated with past management and legume content 3 • Legumes have been reported to improve animal performance (2,9). Results from long-term pasture studies in Virginia (2) indicated steers gained 14% niore when grazing grass-legume mixtures than when grazing N fertilized grass.…”
mentioning
confidence: 99%